Gatorade to assist AIS athletes (Ausport, 2004)
Sports drink manufacturer Gatorade has signed a partnership with the Australian Institute of Sport (AIS) to provide product to AIS athletes and establish a Gatorade sports nutrition fellowship within the AIS Nutrition Department.